GaN based layer structures for sensor application - Pradeep, Ramalingam (2016)
In recent years, research on Gallium nitride material is popular among the semiconductor researchers because of its superior physical properties compared to silicon and other semiconductors. GaN has high band gap, high breakdown field strength, high saturation velocity, high chemical and high radiative inertness, which enable device operation at high voltages, temperatures and challenging environments. Moreover, the wide bandgap of GaN allows its operation in UV range without much degradation due to ageing. In this project, a briefliterature review was conducted on III-Nitrides, and in particular, material properties of GaN were discussed in detail. It is followed by discussion on GaN based metal-semiconductor-metal (MSM) devices and its applications. In the results and discussion part, a brief discussion is presented on the growth of nitride epilayers by molecular beam epitaxy (MBE) followed by the surface and electrical characterization. Finally, photo detection measurements on MSM photodetectors grown by MBE technique are presented and discussed. GaN epilayer structures for photodetector application were grown using plasma-assisted MBE on Si(111) substrate. The epilayers were found crack-free with sub nano-meter roughness. MSM devices were fabricated on different samples and dark current measurements were obtained on all the samples. The sample with lower dark current and higher Schottky barrier was selected for comparison with MSM device fabricated on Ammonia-MBE grown GaN. The results obtained showed PA-MBE Sample has smoother surface morphology compared to Ammonia MBE sample. The samples were further characterized by using the precision semiconductor parameter Analyzer with 4 Point Probe Station to study the I-V properties. The results showed the sample grown by Ammonia MBE has the superior Schottky barrier height, which enables it to have very low leakage current, compared to the sample grown by PA-MBE. Photo current measurements were performed on both samples as a function of wavelength and applied bias. The sample grown using ammonia-MBE showed good responsivity with high UV/Visible rejection ratio and quantum Efficiency. N-rich growth conditions of ammonia-MBE were attributed to lower leakage, good UV responsivity and higher UV/visible rejection ratio.